2016
DOI: 10.1186/s12917-016-0941-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of diagnostic accuracy of renal cortical echogenicity with renal histopathology in dogs and cats, a quantitative study

Abstract: BackgroundRenal cortical echogenicity is routinely evaluated during ultrasonographic investigation of the kidneys. Both in dog and cat previous ex-vivo studies have revealed a poor correlation between renal echogenicity and corresponding lesions. The aim of this study was to establish the in-vivo relationship between renal cortical echogenicity and renal histopathology.ResultsThirty-eight dogs and fifteen cats euthanized for critical medical conditions were included in the study. Ultrasonographic images of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…In the recent years, qualitative and quantitative studies on the cortical echogenicity and the effect of artifacts on its intensity have been performed in healthy dogs. Two more recent publications have tried to eliminate patient and technical related biases, avoiding the comparison with other organs and analyzing the mean gray value in ex vivo and in vivo kidneys under standardized experimental conditions. However, the use of a mean gray scale and strictly standardized ultrasonographic settings was concluded to be poor in distinguishing between normal and pathological kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent years, qualitative and quantitative studies on the cortical echogenicity and the effect of artifacts on its intensity have been performed in healthy dogs. Two more recent publications have tried to eliminate patient and technical related biases, avoiding the comparison with other organs and analyzing the mean gray value in ex vivo and in vivo kidneys under standardized experimental conditions. However, the use of a mean gray scale and strictly standardized ultrasonographic settings was concluded to be poor in distinguishing between normal and pathological kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…On account of its wide availability, low cost, and safety, ultrasound is often the first diagnostic imaging method used for investigation of kidney disease . Several studies have analyzed the sonographic features of the kidneys both in normal dogs and dogs with kidney disease . It is stated in the literature that morphologically abnormal kidneys may function normally, and that morphological alterations may be absent from functionally impaired kidneys, but studies on the association between structural and functional abnormalities are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…kind or extent of sonographic abnormalities needed for inclusion in IRIS stage 1 and many seemingly healthy dogs show slight abnormalities of the kidneys in abdominal sonography (20), a scoring system was used in this study. As previous studies have already shown, there is a poor relation between single sonographic findings and kidney function in dogs(20,21,29) as well as in humans (30). Thus, patients in this study had to achieve at least two points to be included.…”
mentioning
confidence: 89%
“…While correlation of serum SDMA and GFR as the Gold standard for the evaluation of renal function has already been established, correlation between abnormalities in sonography of the kidneys and GFR is still inconclusive. Regarding ultrasonography, a scoring system considering several sonographic parameters of the kidneys was developed, since single criteria of the sonographic appearance of the kidneys have shown little correlation to kidney function in past studies (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%